Compact, quasi-elliptic dual-band bandpass filter with improved isolation - Sovuthy, C. (Institute of Electrical and Electronics Engineers Inc., 2015)
The design of compact and very selective dual band dual-mode filter with improved isolation is introduced in this paper. The two passbands are achieved by connecting two stepped-impedance dual-mode resonators in parallel. Two transmission zeros are obtained on both sides of each passband with the use of the source-load coupling. Theoretical analysis together with experimental prototype is presented. Â© 2015 IEEE.